Translating national discourse into teaching and learning outcomes: Portability and connectivity in developing countries' ICT in education (ICT4E) initiatives. (December 2020) - Stratton, Caroline; Bailey, Diane E; Leonardi, Paul M
We analyze information and communication technology in education initiatives in two South American countries: Bolivia and Uruguay. Utilizing qualitative data collection and analysis methods, we construct a comparative case study to trace the path of how national discourses—in response to the idea of globalization and initiatives promoting computers in education—were translated into policy goals, strategic implementation plans, and teaching and learning practices and outcomes. We document the role of the selected information and communication technology's materiality in terms of portability and connectivity along this translation path. Our findings point to the importance of considering national discourse, often overlooked in information and communication technology in education studies, when examining initiative success and failure, and of conceptualizing materiality as more than merely the infrastructural foundation upon which information and communication technology in education initiatives are built. Understanding the role that materiality plays in interaction with national discourse may be especially important in guiding successful information and communication technology in education initiatives in developing countries, where financial resources are limited.